Penilaian Status Hidrasi - Annisa Dwianggreni Kusuma (Lembaga Penelitian dan Pengabdian Masyarakat Akademi Keperawatan Sandi Karsa (Merger) Politeknik Sandi Karsa, 2020)
Hydration status is a picture of the balance of the entry and exit of water in the body. Water balance is influenced by the amount of food consumed, physical activity, age, and environmental conditions. Dehydration is the loss of large amounts of solute and water. Dehydration can affect the work of the cardio vascular organ and regulate the body's thermoregulation. Dehydration can cause the body to get tired quickly, not excited and interfere with physical work activities. Assessing hydration status is very difficult. There are several methods that can be used to determine the concentration of water in the body using laboratory tests and simple checks. Laboratory examination is in the form of isotope tracer, neutron activation analysis, bioelectrical impedance analysis, while simple examination through changes in body weight, hematological indices, urinary indices, and clinical signs and symptoms. This assessment method has advantages and disadvantages for assessing hydration status. Laboratory tests require facilities and expertise to do so, while simple examinations can be carried out by non-medical personnel and can be carried out in the field. Laboratory tests have good specificity and sensitivity compared to simple examination. Laboratory tests have not been able to describe a person's hydration status. A simple combination of laboratory and laboratory tests is needed to determine a person's hydration status.